Malaysia's Claim to Indonesian Batik: Background and Conflict Resolution - Nina Kurnia Hasanah; Dianti Nabila; Nina Nina; Maria Yovinda Paska; Novia Wulandari; Yusawinur Barella (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This research examines the conflict between Indonesia and Malaysia over the claim to batik as a cultural heritage. Batik, a traditional art form from Indonesia, has long been an important cultural symbol. However, Malaysia’s claim to batik has sparked significant controversy and tension between the two countries. The study emphasizes the importance of understanding cultural heritage disputes in the context of international relations, as they not only involve cultural pride but also economic and diplomatic factors. Using a literature review method, this study analyzes secondary data from books, articles, and scholarly journals to understand the background, developments, and resolutions of this conflict. The key findings highlight Indonesia's successful effort in registering batik as part of UNESCO’s Representative List of the Intangible Cultural Heritage of Humanity in 2009, which provided international recognition and protection for batik. Additionally, the study explores the legal frameworks, including both soft and hard law, that help protect cultural heritage from such claims. The resolution process demonstrates the role of international diplomacy and legal measures in addressing disputes over cultural heritage. The research concludes that while cultural similarities between Indonesia and Malaysia complicate matters, a diplomatic approach supported by international law and UNESCO’s mediation has helped safeguard Indonesia's cultural identity. This study underscores the importance of cooperation in preserving cultural heritage and the essential role of international organizations in managing such conflicts.